Altered lipid peroxidation markers are related to post-traumatic stress disorder (PTSD) and not trauma itself in earthquake survivors - (:unkn) unknown (SPRINGER HEIDELBERG, 2016)
The traumatic life events, including earthquakes, war, and interpersonal conflicts, cause a cascade of psychological and biological changes known as post-traumatic stress disorder (PTSD). Malondialdehyde (MDA) is a reliable marker of lipid peroxidation, and paraoxonase is a known antioxidant enzyme. The aims of this study were to investigate the relationship between earthquake trauma, PTSD effects on oxidative stress and the levels of serum paraoxonase 1 (PON1) enzyme activity, and levels of serum MDA. The study was carried out on three groups called: the PTSD group, the traumatized with earthquake exercise group, and healthy control group, which contained 32, 31, and 38 individuals, respectively. Serum MDA levels and PON1 enzyme activities from all participants were measured, and the results were compared across all groups. There were no significant differences between the PTSD patients and non-PTSD earthquake survivors in terms of the study variables. The mean PON1 enzyme activity from PTSD patients was significantly lower, while the mean MDA level was significantly higher than that of the healthy control group (p < 0.01 for both measurements). Similarly, earthquake survivors who did not develop PTSD showed higher MDA levels and lower PON1 activity when compared to healthy controls. However, the differences between these groups did not reach a statistically significant level. Increased MDA level and decreased PON1 activity measured in PTSD patients after earthquake and may suggest increased oxidative stress in these patients. The nonsignificant trends that are observed in lipid peroxidation markers of earthquake survivors may indicate higher impact of PTSD development on these markers than trauma itself. For example, PTSD diagnosis seems to add to the effect of trauma on serum MDA levels and PON1 enzyme activity. Thus, serum MDA levels and PON1 enzyme activity may serve as biochemical markers of PTSD diagnosis.
Keywords: PTSD; Earthquake; Lipid peroxidation; Biological markers; Oxidative stress; DEFICIT HYPERACTIVITY DISORDER; OXIDATIVE STRESS; ANTIOXIDANT ENZYME; MALONDIALDEHYDE LEVELS; MAJOR DEPRESSION; RESTRAINT STRESS; GENE PON1; ANXIETY; DAMAGE; BRAIN